Hybrid Turbocharged SI engine with Cooled Exhaust Gas Recirculation for Improved Performance. (2016) - Rajeevan, Jinsha; Hans, M.H.; Joseph, Antonio; Kiran, T.S.; Thampi, Gireesh Kumaran
Abstract: Turbocharging with its most advanced forms is left with enough room for the improvement while operating in the lower engine speeds. The impacts of the same have been more visible with petrol engines due to low mass flow rate of exhaust gases. Mathematical model of the SI engine is generated using MATLAB, making use of two-zone combustion model and the thermodynamic relations developed using unsteady flow energy equation. The performance of engine when naturally aspirated, turbocharged and hybrid turbocharged is analysed using the model developed. Enough care is taken to address the occurrence of knock, which determines the extent of turbocharging; using wavelet analysis of the acoustic emissions from the engine. The possibility of technologies such as supercapacitor batteries for hybrid turbocharging, cooled EGR for controlling knocking and dissociation have also been considered in the proposed system. The results exhibit remarkable improvement of 40% in low end torques which pave the way for further downsizing of petrol engines.